Biologic stromal ring to manage stromal melting after intrastromal corneal ring segment implantation. Issue 9 (September 2019) - Jarade, Elias; Issa, Mohamad; Chanbour, Wassef; Warhekar, Pramod
Abstract : N/A: We report a new technique to replace a manufactured poly(methyl methacrylate) (PMMA) ring with a biologic stromal ring fashioned from human corneal donor tissue in eyes with stromal melting above the PMMA ring. The biologic stromal ring is prepared using manual or femtosecond laser trephination of a donor cornea to obtain a 360‐degree ring that is denuded and adjusted to match the PMMA ring being replaced. The biologic ring is attached to the PMMA ring. The PMMA ring is pushed and retrieved from the other side, which installs the biologic ring in place. Six biologic stromal rings were implanted successfully in 5 eyes of 5 patients with previous stromal melting; no complications were reported up to 6 months postoperatively. The biologic stromal ring stopped and healed the melting, prevented further ring complications, and preserved the therapeutic refractive effect of the previously implanted PMMA ring.